Mechanisms Mediating Pediatric Severe Asthma and Potential Novel Therapies - Martin Alonso, Aldara; Saglani, Sejal (Frontiers in Pediatrics, 2017)
Although a rare disease, severe therapy resistant asthma in children is a cause of significant morbidity and results in utilization of approximately 50% of healthcare resources for asthma. Improving control for children with severe asthma is therefore an urgent unmet clinical need. As a group, children with severe asthma have severe and multiple allergies, steroid resistant airway eosinophilia, and significant structural changes of the airway wall (airway remodeling). Omalizumab is currently the only add-on therapy that is licensed for use in children with severe asthma. However, limitations of its use include ineligibility for approximately one-third of patients because of serum IgE levels outside the recommended range, and lack of clinical efficacy in a further one-third. Pediatric severe asthma is thus markedly heterogeneous, but our current understanding of the different mechanisms underpinning various phenotypes is very limited. We know that there are distinctions between the factors that drive pediatric and adult disease since pediatric disease develops in the context of a maturing immune system and during lung growth and development. This review summarizes the current data that gives insight into the pathophysiology of pediatric severe asthma and will highlight potential targets for novel therapies. It is apparent that in order to identify novel treatments for pediatric severe asthma, the challenge of undertaking mechanistic studies using age appropriate experimental models and airway samples from children needs to be accepted to allow a targeted approach of personalized medicine to be achieved.